FACTORS ASSOCIATED WITH VITAMIN D DEFICIENCY IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Warman, Nur Aini Eddy; Shah, Fatimah Zaherah Mohamed; Mohamad, Aimi Fadilah; Awang, Mohd Hazriq; Zainordin, Nur Aisyah; Ghani, Rohana Abdul (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION The prevalence of vitamin D deficiency in the general population in Malaysia was estimated to be 67.4%. In other populations, its prevalence was found to be higher in persons with T2DM. However, vitamin D deficiency has not yet been studied among persons with diabetes in Malaysia. Hypovitaminosis D was found to increase the risk of developing T2DM and is associated with an elevated risk of retinopathy and neuropathy. METHODOLOGY The study aimed to determine the prevalence and factors associated with vitamin D deficiency in patients with T2DM. We conducted a cross-sectional study in patients with T2DM (n=110). The patients were divided into 2 groups; vitamin D deficient (total 25(OD)D3 <50 nmol/L) and vitamin D non-deficient (total 25(OD)D3 ≥50 nmol/L). Serum total 25(OH)D3 was analysed using electrochemiluminescence immunoassay method using Roche Diagnostic laboratory machine. RESULT The prevalence of vitamin D deficiency in our population with T2DM was 48.2% (53/110). In the remaining non-deficient group, 33.6% (37/110) had levels between 50-75 nmol/L, and 18.2% (20/110) had a level ≥75 nmol/L. The baseline age was 57.8 years, diabetes duration was 12 years, and HbA1c was 7.9%. There were significantly higher BMI (29.54 ± 3.29 vs 28.15 ± 4.11 kg/m2 , p=0.05), HbA1c (8.13±1.19 vs 7.74 ± 0.89%, p=0.05), triglycerides (TG) (1.7 (IQR 1.3-2.1) vs 1.3 (IQR 1.15- 1.8) mmol/L, p=0.05), and LDL-c (2.34 ± 0.96 vs 2.03 ± 0.68 mmol/L, p=0.05) in patients with vitamin D deficiency. The vitamin D deficient group showed a larger proportion of patients on insulin ≥0.5 unit/kg/day (58.5 vs 36.8%, p=0.02) and triglycerides ≥1.7 mmol/L (58.5 vs 36.8%, p=0.02). Insulin ≥0.5 unit/kg/day (OR 2.62; 1.1815.817; p=0.02) and BMI ≥25 kg/m2 (OR 4.429; 95%CI 1.311-14.96; p=0.02) were independent predictors for developing vitamin D deficiency. CONCLUSION This study demonstrated a high prevalence of vitamin D deficiency in patients with T2DM. Patients with vitamin D deficiency had a significantly higher BMI, TG, LDL-c, HbA1c, and a higher proportion of patients with insulin ≥0.5 unit/kg. With Insulin ≥0.5 unit/kg and BMI ≥25 kg/m2, the odds of having vitamin D deficiency increased by 2-fold and 4-fold respectively.